Konflik Pertanian antara Komunitas di Desa Watu Nggelek Kecamatan Komodo, Kabupaten Manggarai Barat, Flores, Ntt Tahun 1996 – Sekarang - Yustinus Suhardi Ruman; Antonius Atosökhi Gea (Humaniora, 2010)
Social conflict among community in Indonesia has often happened. In this research we will show that social conflict among community is not always involving two different community about their social background: Community of Dalong Society and Tanah Dereng. They have familial relationship, living in the same economic stratification and their religion is same also. Based on the community characteristic, we attempt to explain the causing of the conflict with using the social change approach in relation with conception of Max Weber about authority. According to Weber there are three ways in which power is commonly transformed into authority: traditional authority, rational-legal authority and charismatic authority. To explain the community conflict in our case, we used conception about traditional and rational-legal authority. Directing by these conception, we analyzed that the conflict happened in one side because of changing in traditional authority. There were groups of community member has not obedience to chief of traditional community, and the other side the government has not ability to operate the legal rule.